Ventures into Viral Cartography: Waffle House, Educational Attainment, and the Social Life of Maps. Issue 1 (2nd January 2020) - Shannon, Jerry; Walker, Kyle E.
Abstract : Viral maps—ones that are shared widely on social media and media outlets—have become an increasingly common part of online conversations about a range of issues. Despite the increasing prevalence of these viral maps, only a few academic researchers have examined the factors leading to their popularity or their social use and effect. In this article, we analyze two case studies of viral maps, a viral tweet about the August 2017 total eclipse and an interactive tool for exploring educational attainment by neighborhood in the United States. By reflecting on our experience as authors of these maps and analyzing the reactions they elicited, we identify several key elements of these maps and their circulation. First, viral maps act as a form of phatic communication, allowing users to restate and react to shared social identities. Second, maps are read from specific times and places, and this spatiotemporal context significantly shapes the reactions of map readers. Finally, viral maps illustrate gaps or improvements in trust between mapmakers and map readers, including questions about map accuracy or the intentions behind the map. We close by considering implications for future research and viral cartography. Key Words: online maps, social networks, viral cartography.